Self-supported mesoporous bitungsten carbide nanoplates electrode for efficient hydrogen evolution reaction. (26th May 2020) - Wu, Shizhao; Chen, Xiaodan; Li, Yuru; Hu, Haifeng; Li, Yuan; Chen, Lihui; Yang, Jiaxing; Gao, Jing; Wang, Xiaojuan; Li, Guohua
Abstract: Developing noble-metal-free electrocatalysts with highly active for the hydrogen evolution reaction (HER) plays a vital role in the future hydrogen economy. Herein, a self-supported mesoporous bitungsten carbide nanoplates electrode (W2 C/W) is in situ fabricated onto tungsten substrate by an anodization followed by a reduction and carbonization process. The W2 C/W electrodes form a sandwich structure with an outer layer constituted of W2 C nanoplates and an inner core of W plate, and the nanoplates are composed of nanoparticles and mesopores. The as-fabricated W2 C/W electrode exhibits superior HER performance in 0.5 M H2 SO4 solution in terms of a low overpotential of ~132 mV at the cathodic current density of 10 mA cm −2, and it also shows outstanding long-term durability after a 10 h test in acidic solution, which indicate that W2 C/W electrodes hold great potential in direct HER application for their low overpotential and high electrocatalytic stability. Graphical abstract: A self-supported bitungsten carbide nanoplate electrode with excellent electrocatalytic properties is in situ fabricated onto tungsten substrate. Image 1 Highlights: Self-supported mesoporous bitungsten carbide nanoplates electrode is fabricated. The bitungsten carbide nanoplates were in situ fabricated onto tungsten foil. The nanoplates composed of nanoparticles and mesopores expose maximum active sites. The HER property of W2 C/W is better than that of micro-nanostructured electrode.